2019
DOI: 10.1038/s12276-019-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment reduces motor and neuropsychiatric phenotypes in the zQ175 mouse model of Huntington disease

Abstract: Huntington disease is a neurodegenerative condition for which there is no cure to date. Activation of AMP-activated protein kinase has previously been shown to be beneficial in in vitro and in vivo models of Huntington’s disease. Moreover, a recent cross-sectional study demonstrated that treatment with metformin, a well-known activator of this enzyme, is associated with better cognitive scores in patients with this disease. We performed a preclinical study using metformin to treat phenotypes of the zQ175 mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 58 publications
9
75
0
Order By: Relevance
“…Treatment with one of the main polyphenolic compounds of green tea, epigallocatechin-3-gallate (EGCG), which failed to improve polyQ-related phenotypes in C. elegans [ 115 ], inhibited the aggregation of Httex1p-93Q in a dose-dependent manner and improved photoreceptor degeneration and motor function [ 153 ]. These results were in agreement with previous results by Sanchis and co-workers showing that AMPK activation by metformin reduces polyQ aggregation in C. elegans [ 127 ].…”
Section: Oxidative Stress and Huntington Diseasesupporting
confidence: 94%
See 2 more Smart Citations
“…Treatment with one of the main polyphenolic compounds of green tea, epigallocatechin-3-gallate (EGCG), which failed to improve polyQ-related phenotypes in C. elegans [ 115 ], inhibited the aggregation of Httex1p-93Q in a dose-dependent manner and improved photoreceptor degeneration and motor function [ 153 ]. These results were in agreement with previous results by Sanchis and co-workers showing that AMPK activation by metformin reduces polyQ aggregation in C. elegans [ 127 ].…”
Section: Oxidative Stress and Huntington Diseasesupporting
confidence: 94%
“…Aside from being a potent antioxidant, EGCG is also an activator of AMP-activated protein kinase (AMPK) [ 125 , 126 ], a master regulator of energy and metabolism. In contrast with the Machiela study, the activation of AMPK using metformin has been shown to improve aggregation of polyQs in worms expressing 40Q in muscle cells [ 127 ]. However, this is not always the case.…”
Section: Oxidative Stress and Huntington Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…Worms expressing polyQs in different tissues helped to uncover many genes modulating the rate of aggregation and/or the toxicity induced by these molecules [ 8 , 11 14 ]. Using neuronal and muscular models of polyQ toxicity in C. elegans , we described AMP-activated protein kinase (AMPK) as a good candidate to manipulate aggregation and toxicity induced by these molecules [ 15 , 16 ]. Moreover, AMPK activation is neuroprotective in in vivo mouse models of HD [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, metformin increases the sensitivity of insulin receptors and decreases glucagon release [9]. Recent reports suggest that metformin may have neuroprotective effects against many neurodegenerative disorders [10,11]. These effects may be attributed to the antioxidant and antiinflammatory properties of metformin together with its ability to restore mitochondrial functions and inhibit apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%